2014
DOI: 10.1002/cmdc.201402521
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Thermodynamic and Kinetic Data in Drug Discovery: Decisive Insight or Increasing the Puzzlement?

Abstract: The prime property to rate the success of hit-to-lead-to-drug optimization in drug discovery is binding affinity. Rational approaches try to relate this property with structure. Affinity can be linked to the thermodynamic property, Gibbs free energy of binding, which itself factorizes into enthalpy and entropy. With respect to kinetic properties, affinity can be associated with the ratio of koff and kon of complex formation. Do these features help to obtain better insight into affinity? The present viewpoint a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 30 publications
(65 reference statements)
2
29
0
Order By: Relevance
“…[14a, 33] The initial assumption that association rate constants are only diffusion controlled andr ather constant within ac ongeneric set of ligands for as pecific target had to be revised. [17,18,34] Indeed, our test subset clearly indicates that the variations of the on-rate constantsw ithin the series of congeneric FimH antagonists 1-4 are more pronounced (for kinITC % 1:16, Ta ble 1A)t han of the off-rate constants (for kinITC % 1:4, Ta ble 1B).…”
Section: Kinetics Of Fimh Ld Bindingmentioning
confidence: 69%
See 1 more Smart Citation
“…[14a, 33] The initial assumption that association rate constants are only diffusion controlled andr ather constant within ac ongeneric set of ligands for as pecific target had to be revised. [17,18,34] Indeed, our test subset clearly indicates that the variations of the on-rate constantsw ithin the series of congeneric FimH antagonists 1-4 are more pronounced (for kinITC % 1:16, Ta ble 1A)t han of the off-rate constants (for kinITC % 1:4, Ta ble 1B).…”
Section: Kinetics Of Fimh Ld Bindingmentioning
confidence: 69%
“…[16] It is surprising that studies on the correlation of molecular structures and their binding kinetics, so-called structure-kinetic relationships (SKRs), are rare. [17] In ar ough approximation, more rotatable bonds and higherm olecular weights correlate with long complex half-lives. [18] Moreover, water-shielded hydrogen bonds also tend to improve the lifetime of proteinligand complexes.…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, wider analysis has demonstrated that the global parameters ΔH and ΔS: integrate multiple contributions of the complex protein-ligand binding process (most importantly the dominant role of the water structure); are very sensitive to influences of the experimental conditions applied in generating the experimental data 9 ; and are subject to the phenomenon of enthalpy-entropy compensation 125 . Retrospective interpretation of differentiated thermodynamic repertoires of ligands is only possible with additional detailed information at hand -most importantly, highresolution crystal structures of the protein-ligand complex containing information on the water network within the binding site 9,126 . Taken together, these factors currently preclude the prospective use of thermodynamics in compound prioritization.…”
Section: Use Of Kinetic and Thermodynamic Data: Expectations And Realmentioning
confidence: 99%
“…In line with this, a study shows that the best-in-class drug is generally more enthalpy favorable than the first-in-class drug by analyzing the thermodynamic profiling of inhibitors of HIV protease and the hydroxy methylglutaryl coenzyme A (HMG-CoA) reductase ( Freire, 2008 ). In conclusion, Δ H serves as a key indicator during hit-to-lead optimization to qualify ligands as candidates for further modifications ( Klebe, 2015 ).…”
Section: Thermodynamic Characterization Of Ligand–target Bindingmentioning
confidence: 99%